Analisis Kompetensi dan Kompensasi terhadap Kinerja Dosen di Universitas Islam Kadiri (UNISKA) Kediri dengan Motivasi sebagai Variabel Intervening - Anas Romzy Hibrida; Suparyadi Suparyadi (Universitas Islam Kadiri, 2020)
The Human Development Index in Indonesia is still relatively low compared to some countries in Southeast Asia that is at rank 110. The key to the high number of such index is the field of education. Islamic University of Kadiri (Uniska) Kediri have a role in improving the quality of human resources through higher education. The quality of education and the learning process in Uniska would success depends on the lecturer performance, which is affected by several factors, among others: Competence, Compensation and Motivation owned and accepted by the lecturers Uniska. This study aims to determine the significance of the effect of competence, compensation to the performance of lecturers in Uniska Kediri with motivation as an intervening variable. This research is quantitative data collection techniques in the form of a questionnaire to 69 lecturers Uniska, with the Likert scale 1-5 range. The sampling technique used in this study is simple random sampling. Data analysis tool used in this study are Validity, Test Multicolinearity, Test Heterocedastity, Analysis Descriptive, Analysis Inferential, Multiple Linear Regression Analysis, The Coefficient Of Determination, Simultant Test (F), Partial test (t) and Path Analysis with SPSS calculations 23:00 for Windows. The study states that Competency and Compensation has significant effect on motivation, Competence has not significant effect on the performance of lecturers, Compensation and motivation has significant effect on the performance of lecturers of UNISKA Kediri.